Efektivitas Ekstrak Daun Serai (Cymbopogon citratus) terhadap Pertumbuhan Staphylococcus aureus pada Basis Akrilik Piranti Ortodonti Lepasan - Davin Davin; Desi Watri; Meilysa Br Sembiring (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aimed to evaluate the antibacterial effectiveness of lemongrass (Cymbopogon citratus) extract against Staphylococcus aureus on the acrylic base of removable orthodontic appliances. This laboratory experimental research employed a post-test only control group design using acrylic samples previously inoculated with Staphylococcus aureus ATCC 25923. Four treatment groups were tested: 40% and 50% lemongrass leaf extract, 0.2% chlorhexidine gluconate as the positive control, and DMSO as the negative control. Bacterial colony counts were measured using the total plate count method after the incubation period. The results showed significant differences among the groups (p ≤ 0,05), with the 50% concentration producing the lowest colony count and exhibiting the strongest antibacterial activity. The 40% concentration also demonstrated inhibitory effects, although not as strongly as the 50% concentration. When compared with the positive control, the 50% lemongrass extract showed an effectiveness nearly equivalent to chlorhexidine. These findings indicate that lemongrass extract, particularly at a 50% concentration, can be utilized as a natural disinfectant for removable orthodontic appliances to reduce bacterial counts